Killashandra - McCaffrey, Anne (Ballantine Books, 1985)
The exhilarating adventures of Anne McCaffrey's best selling Crystal Singer series continue with Killashandra, a story that mixes interplanetary political intrigue with passionate romance. In this installment, Killashandra Ree's crystal claim has been exhausted, forcing her to take a new assignment and leave her new lover back on their native Ballybran. She goes undercover on a distant, desolate planet, searching desperately for the crystal that will save her - and, quite possibly, the fate of the entire universe.